Requirements Elicitation with and for Older Adults - Sustar, Helena; Pfeil, Ulrike; Zaphiris, Panayiotis (My University, 2008)
The study investigated the strengths and weaknesses of existing user-centered design (UCD) methods for eliciting requirements from older adults. A case study in which older people are involved in designing, developing, and evaluating a virtual-garden prototype. Users could potentially employ this device (which has an interface that resembles a real garden) as an empathic information appliance that would provide weather forecasts and help control smart devices and assistive technologies. Creativity-oriented techniques are suggested to designers, developers, and engineers when creating products so that older people are included in the market consideration.
Keywords: Design; Augmented reality; Human computer interaction